(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Advances in internet technologies (ITs) and on line social networks have made extra blessings to humanity. on the equal time, the darkish facet of this boom/benefit has brought about extended hate speech and terrorism as most commonplace and effective threats globally. Hate speech is an offensive type of conversation mechanism that expresses an ideology of hate the use of stereotypes. Hate speech goals specific covered characteristicswhich include gender, faith, race, and disability. manipulate of hate speech may be made the usage of exclusive countrywide and international legal frameworks. Any intentional act directed towards lifestyles or related entities inflicting a not unusual chance is referred to as terrorism. there’s a not unusual practice of discussing or debating hate speech and terrorism one by one. in the recent beyond, most of the studies articles have discussed both hate speech or terrorism. Hate speech is a type of terrorism and follows an incident or trigger event of terrorism. on-line social networks are the end result of ITs and advanced unexpectedly through the popularity amongst adolescents. As both the activities are close to to close and makes use of on-line social networks, the collective dialogue is suitable. consequently, we have a overview on hate speech with specific training and terrorism with cyber use within the framework of on line social networks. With the assist of blended effort from the government, the net provider providers (ISPs) and online social networks, the proper policies can be framed to counter each hate speech and terrorism successfully and correctly.